206 Cost-benefit analysis of fall injuries prevented by a programme of home modifications. (1st September 2016) - Keall, Michael D; Pierse, Nevil; Howden-Chapman, Philippa; Guria, Jagadish; Cunningham, Chris; Baker, Michael G
Abstract : Background: Injuries due to falls in the home amongst the general population impose a huge social and economic cost on society. We previously found important safety benefits of home modifications such as handrails for steps and stairs, grab rails for bathrooms, outside lighting, edging for outside steps and slip-resistant surfacing for outside surfaces such as decks. Methods: Following a single-blinded cluster randomised controlled trial (the HIPI trial), we analysed insurance payments for medically-treated home fall injuries. The benefits in terms of the value of DALYs averted and social costs of injuries were extrapolated to a national level and compared with the costs of the intervention. Results: Costs per injury per time exposed to the modified homes compared to the unmodified homes showed a reduction in the insurer costs of home fall injuries of 36% (95% CI: 5%–59%). The social benefits of injuries prevented were estimated to be at least 9 times the costs of the intervention. The benefit cost ratio can be at least doubled for older people and those with a prior history of fall injuries. Conclusions: This is the first randomised controlled trial to our knowledge to examine the benefits of home modification for reducing fall injury costs in the general population. The results show a convincing economic justification for undertaking relatively low-cost home repairs and installation of safety features.